A new genus of Diplommatinidae from the Andaman Islands (Gastropoda: Caenogastropoda: Cyclophoroidea). (2nd July 2020) - Páll-Gergely, Barna
ABSTRACT: Examination of the syntypes of Pupa ( Pupisoma ) constrictus Godwin-Austen, 1895 revealed that this species does not belong to the eupulmonate Pupilloidea, but to the caenogastropod Diplommatinidae. Based on conchological characters it could not be placed to any of the existing diplommatinid genera, therefore a new genus, Moderata n. gen. is erected, which is characterised by a conical shell, a discontinuous aperture and most importantly, a conspicuous constriction half a whorl behind the aperture. Pupisoma bilamellatum Benthem Jutting, 1958 and P. unilamellatum Benthem Jutting, 1958 are moved to the assimineid genus Acmella W. T. Blanford, 1869.